1992
DOI: 10.1111/j.1540-8159.1992.tb03067.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vagal Nerve Electrostimulation on the Power Spectrum of Heart Rate Variability in Man

Abstract: The power spectrum of heart rate variability contains low frequency (LF = 0.08-0.12 Hz) and high frequency (HF = 0.18-0.30 Hz) components said to represent neurocardiac rhythms. To verify whether such a relationship exists we report a unique study where the heart rate autospectrum was determined in a 28-year-old epileptic male patient with an implanted vagal electrical stimulator. The stimulator was activated at 20 Hz, 300 microseconds pulse, and 1.25 V. Continuous ECG and respiratory waveform records were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 19 publications
0
34
2
Order By: Relevance
“…These results suggest that the HF component in HRV may not reflect the intensity of VS or probably vagal tone, irrespective of the presence of an intact or denervated autonomic nerve system. In contrast, Kamath et al [10] have reported that continuous VS for more than several hours increased HF power, but did not prolong the RR interval in only one patient with intractable epilepsy. The observed discrepancy may be attributable to setting, including anesthesia, denervation or stimulation protocol.…”
Section: Discussionmentioning
confidence: 93%
“…These results suggest that the HF component in HRV may not reflect the intensity of VS or probably vagal tone, irrespective of the presence of an intact or denervated autonomic nerve system. In contrast, Kamath et al [10] have reported that continuous VS for more than several hours increased HF power, but did not prolong the RR interval in only one patient with intractable epilepsy. The observed discrepancy may be attributable to setting, including anesthesia, denervation or stimulation protocol.…”
Section: Discussionmentioning
confidence: 93%
“…This dysfunction results in higher morbidity and mortality in patients with epilepsy than in those without epilepsy (17). Frequency-domain analysis of heart rate variability (HRV) is a sophisticated and noninvasive tool for detecting autonomic regulation of the heart (11,14,(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…A unique in vivo experiment that illustrates this balance was conducted in patients with an implanted electrical vagus nerve stimulator for the treatment of epilepsy. 28 In these subjects, HF power and HF/LF ratio were greatly increased when the stimulator was activated, illustrating that these measures are reliable indicators of vagal activity in humans. Nevertheless, caution should be taken when evaluating these parameters because other workers have indicated that parasympathetic outflow and other factors such as baroreceptor activity also influence LF power, thus stating that LF power represents a combination of sympathetic and parasympathetic input.…”
Section: Measurement Of Autonomic Nervousmentioning
confidence: 98%